Advanced imaging in acute and chronic deep vein thrombosis - Karande, Gita Yashwantrao; Hedgire, Sandeep S.; Sanchez, Yadiel; Baliyan, Vinit; Mishra, Vishala; Ganguli, Suvranu; Prabhakar, Anand M. (Cardiovascular Diagnosis and Therapy; Vol 6, No 6 (December 29, 2016): Cardiovascular Diagnosis and Therapy (Advanced Venous Imaging and Image-guided Venous Interventions), 2016)
Deep venous thrombosis (DVT) affecting the extremities is a common clinical problem. Prompt imaging aids in rapid diagnosis and adequate treatment. While ultrasound (US) remains the workhorse of detection of extremity venous thrombosis, CT and MRI are commonly used as the problem-solving tools either to visualize the thrombosis in central veins like superior or inferior vena cava (IVC) or to test for the presence of complications like pulmonary embolism (PE). The cross-sectional modalities also offer improved visualization of venous collaterals. The purpose of this article is to review the established modalities used for characterization and diagnosis of DVT, and further explore promising innovations and recent advances in this field.